The Effect Of Current Ratio, Debt To Equity Ratio And Roa On Stock Prices In Sharia Based Manufacturing Companies In Indonesia Stock Exchange - Isra Hayati; Dedek Hardianti Saragih; Saparuddin Siregar Siregar (Proceeding International Seminar of Islamic Studies, 2019)
This study was made to find out how the influence of the Financial Ratio on Stock Prices in Sharia-Based Manufacturing Companies in the Indonesia Stock Exchange for the period 2014-2018. The approach taken is an associative approach. While the types of data used in this study are quantitative data in the form of financial statements from 2014 to 2018. The samples used are eight Sharia-Based Manufacturing companies listed on the Indonesia Stock Exchange.The results of this study prove that partially Current Ratio has no significant effect on stock prices. This is evidenced by the value of tcount of -0.826, which is smaller than the value of ttable of 2.024. Then partially the Debt to Equity Ratio also has no significant effect on the Stock Price. This is evidenced by the value of t count of -0.7774 smaller than the value of ttable of 2.026. While the Return On Assets have a significant effect on Stock Prices. This is evidenced by the value of t-count Return On Assets of 6.042 greater than the value of t table of 2.026. Simultaneously shows that Current Ratio, Debt to Equity Ratio and Return On Assets. This is evidenced by the value of Fcount of 13,649 greater than the value of F table of 2.87.